Management Strategies for Posttransplant Diabetes Mellitus after Heart Transplantation: A Review. (29th January 2018) - Cehic, Matthew G.; Nundall, Nishant; Greenfield, Jerry R.; Macdonald, Peter S.
Abstract : Posttransplant diabetes mellitus (PTDM) is a well-recognized complication of heart transplantation and is associated with increased morbidity and mortality. Previous studies have yielded wide ranging estimates in the incidence of PTDM due in part to variable definitions applied. In addition, there is a limited published data on the management of PTDM after heart transplantation and a paucity of studies examining the effects of newer classes of hypoglycaemic drug therapies. In this review, we discuss the role of established glucose-lowering therapies and the rationale and emerging clinical evidence that supports the role of incretin-based therapies (glucagon like peptide- (GLP-) 1 agonists and dipeptidyl peptidase- (DPP-) 4 inhibitors) and sodium-glucose cotransporter 2 (SGLT2) inhibitors in the management of PTDM after heart transplantation. Recently published Consensus Guidelines for the diagnosis of PTDM will hopefully lead to more consistent approaches to the diagnosis of PTDM and provide a platform for the larger-scale multicentre trials that will be needed to determine the role of these newer therapies in the management of PTDM.